First simplify the expression as much as possible.
2x - x + 5
2x - x = x
x + 5
There are two terms, x and 5. expressions that have two terms are known as binomials
binomials should be your answer.
hope this helps
This might not be correct but....
I’m going to use rounding,
42 x 2 = 84
84 divides by 3 = 28,
Which is near 30......So the number of people in the group is rounding to about 2 people.
Mean is the average of all numbers
(5+2+7+8+2+5+3)/7
Mean is 4.57
Median is the middle score so we have to arrange all the numbers from lowest to highest
2, 2, 3, 5, 5, 7, 8
Median is 5
Given:
The expression: (1 + x)^n
The Binomial Theorem is used to predict the products of a binomial raised to a certain power, n, without multiplying the terms one by one.
The following formula is used:
(a + b)^n = nCk * a^(n-k) * b^k
we have (1 +x)^n,
where a = 1
b = x
let n = 4
First term, k = 1
4C1 = 4
first term: 4*(1^(4-1))*x^1
Therefore, the first term is 4x. Do the same for the next three terms.
2nd term: k =2
3rd term: k = 3
4th term: k = 4
<span />
Answer:
24
Step-by-step explanation:
1.-12
2.-12×2=-24
3.24